Zasady rachunkowości w regulacjach międzynarodowych i w polskim prawie bilansowym - Buczkowska, Anna (Accounting Principles in International Standards and Polish Balance-Law, 2005)
The purpose of accounting is to deliver to the wide range of users information about company's financial and property situation. Compiling this kind of information you should obey general accounting principles which are defined by international standards and by Polish balance-law. This article presents accounting principles in mentioned regulations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 151-159